Cementitious cellular composites with auxetic behavior. (August 2020) - Xu, Yading; Zhang, Hongzhi; Schlangen, Erik; Luković, Mladena; Šavija, Branko
Abstract: Auxetic behavior refers to material with negative Poisson's ratio. In this research, a new type of cementitious auxetic material is developed. A novel crack bridging auxetic mechanism is discovered which is in contrast with a local buckling mechanism commonly employed to trigger auxetic behavior. Taking advantage of 3D printing techniques, cementitious cellular composite (CCC) specimens with auxetic cellular structures were produced. Meanwhile, cementitious materials with different fiber content were used as constituent material. Uniaxial compression and cyclic loading tests were performed on the CCCs. Experiments show that with proper constituent material, CCCs can exhibit auxetic behavior which is induced by crack bridging process of the cementitious constituent material. In addition, strain hardening behavior can be identified in the stress-strain curve under uniaxial compression and consequently high specific energy absorption is obtained. Furthermore, 2.5% of reversible deformation which is significantly higher than conventional cementitious materials under cyclic loading is obtained within 25, 000 cycles. Obvious fatigue damage is observed in the first 3000 cycles, afterwards signs of mechanical properties recovering can be found. The discovered auxetic mechanism indicates a new designing direction for brittle materials to achieve auxetic behaviors.